Global corporate strategies and local interests? (On the discussion in Europe) - Muller, Hans-Erich (Universiti Utara Malaysia, 1997)
The balance of economic power is beginning to shift. A lively debate is in progress in Europe about the social and political consequences of growing competition from emerging Southeast Asian countries. This article provides a broad outline of the background behind the dynamism and the driving forces of globalization. Leading corporations adapt themselves to the changing environmental conditions by using the strategies of global localization and decentralized organizational structures (lean production, total quality management, reengineering etc.). Their success, however, depends on the development of the relevant institutions, not the least for regulating conflicts.